Radiation-Induced Sarcoma of the Head and Neck: A Review of the Literature - Giannini, Lorenzo; Incandela, Fabiola; Fiore, Marco; Gronchi, Alessandro; Stacchiotti, Silvia; Sangalli, Claudia; Piazza, Cesare (Frontiers in Oncology, 2018)
In the last decades, radiotherapy (RT) has become one of the cornerstones in the treatment of head and neck (HN) malignancies and has paralleled an increase in long-term patient survival. This lead to a concomitant increase in the incidence of radiation-induced sarcomas (RIS) of the irradiated field, with an annual rate up to 0.17%. The new techniques of irradiation do not seem to influence the risk of RIS of the HN (RISHN), which mainly develop within the middle-dose field. The median latency of RISHN after RT is 10-12 years and osteosarcoma is the most represented histotype, even though there is a high variability in time of occurrence and histological features observed. There is no clear evidence of predisposing factors for RISHN, and genetic findings so far have not revealed any common mutation. Early clinical diagnosis of RISHN is challenging, since it usually occurs within fibrotic and hardened tissues, while radiological findings are not pathognomonic and able to differentiate them from other neoplastic entities. Given the highly aggressive behavior of RISHN and its poor sensitivity to chemotherapy, radical surgery is the most important prognostic factor and the only curative option at present. Nevertheless, the anatomy of the HN district and the infiltrative nature of RIS do not always allow radical intervention. Therefore, a wise integration with systemic therapy and, when feasible, re-irradiation should be performed. Future findings in the genomic features of RISHN will be crucial to identify a possible sensitivity to specific drugs in order to optimize a multimodal treatment that will be ideally complementary to surgery and re-irradiation.